Racial and Ethnic Differences in Homework Time among U.S. Teens. (December 2022) - Dunatchik, Allison; Park, Hyunjoon
Along with intensified competition for college admissions, U.S. teens increasingly spend more time on educational activities. Homework can be a particularly important component of educational time for economically disadvantaged and racial/ethnic minority students who have limited access to private sources of learning beyond the classroom. This study uses data from the American Time Use Survey and the Programme for International Student Assessment to compare homework time by race/ethnicity and examine the factors that explain these differences. We extend existing literature to consider explanations beyond demographic and family background. Our ordinary least squares (OLS) results show that family background accounts for the difference in homework time between Hispanic and White students and partially explains the difference between Black and White students, with students' academic characteristics or school fixed effects explaining the remaining gap. While these factors partially account for Asian students' greater time spent on homework than their White peers, a substantial gap remains.